2021
DOI: 10.3389/fmicb.2021.735562
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Complexity: Optimized Systems to Study the Role of the Gut Microbiome in Host Physiology

Abstract: The profound impact of the gut microbiome on host health has led to a revolution in biomedical research, motivating researchers from disparate fields to define the specific molecular mechanisms that mediate host-beneficial effects. The advent of genomic technologies allied to the use of model microbiomes in gnotobiotic mouse models has transformed our understanding of intestinal microbial ecology and the impact of the microbiome on the host. However, despite incredible advances, our understanding of the host-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 236 publications
(349 reference statements)
0
4
0
Order By: Relevance
“…Probiotics are crucial in maintaining a healthy GM, which is essential for overall female wellness. Earlier studies have shown that probiotics can improve digestion, enhance immunity, and reduce inflammatory responses [1][2][3]. Moreover, probiotics help treat a range of ailments, including diarrhea and urinary tract infections.…”
Section: Probiotics and Women's Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics are crucial in maintaining a healthy GM, which is essential for overall female wellness. Earlier studies have shown that probiotics can improve digestion, enhance immunity, and reduce inflammatory responses [1][2][3]. Moreover, probiotics help treat a range of ailments, including diarrhea and urinary tract infections.…”
Section: Probiotics and Women's Healthmentioning
confidence: 99%
“…GM metabolizes undigested meal remnants, from which more energy is derived. A balanced relationship between bacterial strains and our bodies enables homeostasis [3]. The diversity of natural flora varies with age, health, living situations, and the use of antibacterial, disinfectants, and certain cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome plays an integral role in healthy development, aging, and multiple disease contexts 1 . However, integrated analyses of host-microbiome ecosystems in vivo have been difficult to achieve in part due to the lack of relevant model systems 2 and substantial differences across patients 3,4 . Recently, it has been shown that microbial nucleic acids are captured in polyA-selected RNA sequencing of clinical samples from humans 57 .…”
Section: Main Textmentioning
confidence: 99%
“…The microbiome plays an integral role in healthy development, aging, and multiple diseases, however the nature of its influence in many contexts remains poorly understood 1 . This is because integrated analyses of host-microbiome ecosystems in vivo have been difficult to achieve in part due to the lack of relevant model systems 2 , technological barriers to directly profiling host-microbial interactions at high resolution in human tissues, and substantial heterogeneity across patients 3,4 .…”
Section: Main Textmentioning
confidence: 99%